Heaven - Johnson, Angela, 1961- (New York : Simon Pulse, 2004)
Fourteen-year-old Marley's seemingly perfect life in the small town of Heaven is disrupted when she discovers that her father and mother are not her real parents.
Keywords: Adoption -- Fiction; Parent and child -- Fiction; African Americans -- Fiction; Adoption -- Juvenile fiction; Parent and child -- Juvenile fiction; African Americans -- Juvenile fiction